The Early Ordovician (Floian) bathyurid trilobite Jimlochaspis n. gen., with species from western Utah and Greenland - Jonathan M. Adrain; Francesc Pérez-Peris (Palaeoworld, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Environmental Drivers of Recruitment Variability in Narrow‐Barred Spanish Mackerel Scomberomorus commerson Lacépède, 1800 - Susannah M. Leahy; Joanne Langstreth; Rik C. Buckworth; Peri Subritzky; Olivia J. Whybird; Sam M. Williams; Lucas I. Sumpter; Jonathan D. Mitchell (Fisheries Oceanography, 2026)
Understanding the effects of environmental conditions on fisheries resources is crucial for guiding the effective assessment and management of fish stocks. Previously assessed as depleted, the narrow‐barred Spanish mackerel fishery on the east coast of Queensland, Australia, is under management intervention to rebuild the stock. In this study, we use long‐term age composition data to reconstruct 24 years of historic year class strength and explore a broad range of potential environmental influences on recruitment variability in the fishery. Year class strength was extremely well captured (76%–84% deviance explained) by generalised additive models containing just four environmental indices. Recurring key environmental indices in top models included environmental conditions prior to spawning (large scouring flood events during the wet season before spawning and cool winter sea surface temperature immediately prior to spawning), during spawning (unseasonal flooding near the spawning grounds), during larval dispersal and proxies for food availability for juvenile Spanish mackerel. These results have since been used to hindcast recruitment variability in the fishery prior to the collection of the age‐composition data to better understand historic fluctuations in the fishery, and can also be incorporated into management strategies for rebuilding the stock.

Drivers and spatial modelling of soil organic carbon in Argentinian subtropical forests: Path towards sustainable management and climate mitigation - Silvina M. Manrique; Juan Gaitán; Ezequiel Balducci; Flavio Speranza; Cecilia Blundo; Ignacio Gasparri; Miguel A. Zavala; Pablo L. Peri (Forest Ecology and Management, 2025)

Fire and roller-chopping effects on forage production, plant diversity, and carbon storage in Neltuma woodlands of the Central Monte, Argentina - Pablo A. Meglioli; Marina A. Morsucci Labiano; Sebastián Mora; Leandro M. Alvarez; Gualberto Zalazar; Pablo L. Peri; Pablo E. Villagra (Agriculture, Ecosystems & Environment, 2025)

Neurogenomic landscape associated with status‐dependent cooperative behaviour - Peri E. Bolton; T. Brandt Ryder; Roslyn Dakin; Jennifer L. Houtz; Ignacio T. Moore; Christopher N. Balakrishnan; Brent M. Horton (Molecular Ecology, 2025)
The neurogenomic mechanisms mediating male–male reproductive cooperative behaviours remain unknown. We leveraged extensive transcriptomic and behavioural data on a neotropical bird species ( Pipra filicauda ) that performs cooperative courtship displays to understand these mechanisms. In this species, the cooperative display is modulated by testosterone, which promotes cooperation in non‐territorial birds, but suppresses cooperation in territory holders. We sought to understand the neurogenomic underpinnings of three related traits: social status, cooperative display behaviour and testosterone phenotype. To do this, we profiled gene expression in 10 brain nuclei spanning the social decision‐making network (SDMN), and two key endocrine tissues that regulate social behaviour. We associated gene expression with each bird's behavioural and endocrine profile derived from 3 years of repeated measures taken from free‐living birds in the Ecuadorian Amazon. We found distinct landscapes of constitutive gene expression were associated with social status, testosterone phenotype and cooperation, reflecting the modular organization and engagement of neuroendocrine tissues. Sex‐steroid and neuropeptide signalling appeared to be important in mediating status‐specific relationships between testosterone and cooperation, suggesting shared regulatory mechanisms with male aggressive and sexual behaviours. We also identified differentially regulated genes involved in cellular activity and synaptic potentiation, suggesting multiple mechanisms underpin these genomic states. Finally, we identified SDMN‐wide gene expression differences between territorial and floater males that could form the basis of ‘status‐specific’ neurophysiological phenotypes, potentially mediated by testosterone and growth hormone. Overall, our findings provide new, systems‐level insights into the mechanisms of cooperative behaviour and suggest that differences in neurogenomic state are the basis for individual differences in social behaviour.

Preliminary evidence suggests that interrow cover crops may enrich potentially beneficial bacterial groups that confer soil-suppressive capacity against the olive pathogen Verticillium dahliae - Sandra Tienda; Mariia Kolodeznaia; Víctor J. Carrión; Ana Lia Gayan-Quijano; Belén Delgado-Martín; Ben O. Oyserman; Francisco Javier Peris-Felipo; Jose Antonio Gutiérrez-Barranquero; Francisco M. Cazorla (Rhizosphere, 2025)

3D Models as a Source for Neuroanatomy Education: A Stepwise White Matter Dissection Using 3D Images and Photogrammetry Scans - André S. B. Oliveira; João Vitor A. Fernandes; Vera Louise F. A. Figueiredo; Luciano C. P. C. Leonel; Megan M. J. Bauman; Michael J. Link; Maria Peris-Celda (Brain Topography, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Ordovician paleobiogeography of the Suborder Cheirurina (Trilobita) - Francesc Pérez-Peris; Jonathan M. Adrain; Allison C. Daley (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Exploring intergenerational differences in consumer acceptance of insects-fed farmed fish - M.T. Trentinaglia; M. Adler; M. Peri; L. Panzone; L. Baldi (Food Quality and Preference, 2024)

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Threatened and Priority listed Melaleuca species from Western Australia display high susceptibility to Austropuccinia psidii in controlled inoculations - Alyssa M. Martino; Robert F. Park; Peri A. Tobias (Australasian Plant Pathology, 2024)
Austropuccinia psidii causes rust disease on species within the family Myrtaceae. It was first detected in Australia in 2010, with the first detection in Western Australia in 2022. While species within the genus Melaleuca from eastern Australia show variable responses to the pathogen, little is known of the response of species from Western Australia. This study established that 13 previously unscreened species of Melaleuca , including Threatened and Priority listed species that were grown from seeds sourced from Western Australian populations, were susceptible four months post-germination to the pandemic strain of the pathogen. The proportion of highly susceptible plants within a single species ranged from 2 to 94%, with several species displaying highly variable levels of resistance to A. psidii . These results highlight the importance of disease screening and may direct conservation efforts.

Palliative Effects of Kaolin on Citrus Plants Under Controlled Stress Conditions of High Temperature and High Light Intensity - Fátima Terán; Vicente Vives-Peris; María F. López-Climent; Aurelio Gómez-Cadenas; Rosa M. Pérez-Clemente (Journal of Plant Growth Regulation, 2024)
Under field conditions high temperatures are usually associated to high light intensity for periods of time that are getting longer because of global warming caused by climate change. These adverse conditions lead to significant reductions in yield and fruit quality in crops of great economic relevance such as citrus. In this work, the effect of high temperatures and high light intensity occurring alone or simultaneously has been studied in Carrizo citrange plants, a citrus genotype widely used as a rootstock, and the mitigating effect of kaolin (KL) evaluated. The combined stress conditions affected the plants in a unique manner at both, physiological and hormonal regulation levels, different to the effects of each individual stress. KL alleviated the deleterious effect of combined stress in different ways: (i) reducing leaf damage and abscission, (ii) improving physiological and gas exchange parameters, (iii) decreasing foliar proline content, (iv) increasing chlorophyll content, (v) preventing carotenoid degradation, and (vi) modulating levels of hormones and their precursors involved in plant responses to stress [abscisic acid (ABA), salicylic acid (SA), cinnamic acid (CA), indole-3-acetic acid (IAA), jasmonic acid (JA) and 12-oxophytodienoic acid (OPDA)].

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

In-state generation requirements and the acceptability of renewable portfolio standards - Todd L. Cherry; Peri M. Brimley; Joseph D. Longuevan; Linda Thunström (Utilities Policy, 2023)

Involvement of Abscisic Acid and Jasmonic Acid Biosynthesis-related Genes in Cucurbita pepo L. Tolerance to Trace Metal Stress - Oumayma Labidi; Rim Kouki; Rosa M. Pérez-Clemente; Aurelio Gómez-Cadenas; Noomene Sleimi; Vicente Vives-Peris (Water, Air, & Soil Pollution, 2023)
Trace metal induced stress is an abiotic factor that limits crop yield, having the additional hazard of their accumulation along trophic chain. This fact supposes an emerging problem concerning the health of the population in the case of edible plants such as Cucurbita pepo (zucchini). Most of the plant physiological responses to this adverse situation are regulated by phytohormones, being abscisic acid (ABA) and jasmonic acid (JA) the most important ones, which biosynthesis comprises a key step in this hormone-mediated signaling. In this work, genes involved in ABA and JA biosynthesis have been searched in the zucchini genome, and their expression has been analyzed in leaves of adult plants subjected to Cd- or Ni-induced stress. The results showed the higher sensitivity of zucchini plants to Ni in comparison to Cd, with a higher phenotypic affection and a major decrease of total dry weight. The study of the expression of 12 target genes (5 related to JA biosynthesis and 7 related to ABA biosynthesis), allowed determining a similar genetic response in C. pepo to these metals. The results extend our knowledge of the role of phytohormones on trace metal stress tolerance. Among all the studied genes, the main ones involved in plant responses to trace metal stress were the ABA-related CpAAO3 , CpZEP , and CpNCED4 , as well as the JA-related CpLOX2 , CpOPR3 , CpAOS2 , and CpJAR1 . These results provide relevant information to be used in future breeding programs.

Variable retention harvesting and climate variations influence over natural regeneration dynamics in Nothofagus pumilio forests of Southern Patagonia - Julián Rodríguez-Souilla; Juan M. Cellini; María V. Lencinas; Fidel A. Roig; Jimena E. Chaves; Marie-Claire Aravena Acuña; Pablo L. Peri; Guillermo J. Martínez Pastur (Forest Ecology and Management, 2023)

Compositional shifts of alpine plant communities across the high Andes - F. Cuesta; J. Carilla; L. D. LLambí; P. Muriel; M. V. Lencinas; R. I. Meneses; K. J. Feeley; H. Pauli; N. Aguirre; S. Beck; A. Bernardi; S. Cuello; et al. (Global Ecology and Biogeography, 2023)
Aim Climate change is transforming mountain summit plant communities worldwide, but we know little about such changes in the High Andes. Understanding large‐scale patterns of vegetation changes across the Andes, and the factors driving these changes, is fundamental to predicting the effects of global warming. We assessed trends in vegetation cover, species richness (SR) and community‐level thermal niches (CTN) and tested whether they are explained by summits' climatic conditions and soil temperature trends. Location High Andes. Time period Between 2011/2012 and 2017/2019. Major taxa studied Vascular plants. Methods Using permanent vegetation plots placed on 45 mountain summits and soil temperature loggers situated along a ~6800 km N‐S gradient, we measured species and their relative percentage cover and estimated CTN in two surveys (intervals between 5 and 8 years). We then estimated the annual rate of changes for the three variables and used generalized linear models to assess their relationship with annual precipitation, the minimum air temperatures of each summit and rates of change in the locally recorded soil temperatures. Results Over time, there was an average loss of vegetation cover (mean = −0.26%/yr), and a gain in SR across summits (mean = 0.38 species m 2 /yr), but most summits had significant increases in SR and vegetation cover. Changes in SR were positively related to minimum air temperature and soil temperature rate of change. Most plant communities experienced shifts in their composition by including greater abundances of species with broader thermal niches and higher optima. However, the measured changes in soil temperature did not explain the observed changes in CTN. Main conclusions High Andean vegetation is changing in cover and SR and is shifting towards species with wider thermal niche breadths. The weak relationship with soil temperature trends could have resulted from the short study period that only marginally captures changes in vegetation through time.

Amber and the Cretaceous Resinous Interval - Xavier Delclòs; Enrique Peñalver; Eduardo Barrón; David Peris; David A. Grimaldi; Michael Holz; Conrad C. Labandeira; Erin E. Saupe; Christopher R. Scotese; Mónica M. Solórzano-Kraemer; Sergio Álvarez-Parra; Antonio Arillo; et al. (Earth-Science Reviews, 2023)

Seed fall and leaf litter relationships in Nothofagus pumilio forests: changes according to retention levels and years after harvesting - Julián Rodríguez-Souilla; María V. Lencinas; Juan M. Cellini; Jimena E. Chaves; Fidel A. Roig; Pablo L. Peri; Guillermo J. Martínez Pastur (Trees, 2023)

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Silvopastoral use of Nothofagus antarctica forests in Patagonia: impact on soil microorganisms - V. Gargaglione; M. Gonzalez Polo; J. Birgi; S. Toledo; P. Peri (Agroforestry Systems, 2022)

Changes in forest structure modify understory and livestock occurrence along the natural cycle and different management strategies in Nothofagus antarctica forests - Guillermo José Martínez Pastur; Juan M. Cellini; Jimena E. Chaves; Julián Rodríguez-Souilla; Julieta Benitez; Yamina M. Rosas; Rosina M. Soler; María V. Lencinas; Pablo L. Peri (Agroforestry Systems, 2022)

Novel MAPK/AKT-impairing germline NRAS variant identified in a melanoma-prone family - Kevin M. Brown; Mai Xu; Michael Sargen; Hyunbum Jang; Mingzhen Zhang; Tongwu Zhang; Bin Zhu; Kristie Jones; Jung Kim; Laura Mendoza; Nicholas K. Hayward; Margaret A. Tucker; et al. (Familial Cancer, 2022)

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Reward processing in trichotillomania and skin picking disorder - Jon E. Grant; Tara S. Peris; Emily J. Ricketts; Richard A. I. Bethlehem; Samuel R. Chamberlain; Joseph O’Neill; Jeremiah M. Scharf; Darin D. Dougherty; Thilo Deckersbach; Douglas W. Woods; John Piacentini; Nancy J. Keuthen (Brain Imaging and Behavior, 2022)

Poor Sleep Quality in Medical Students is Related to Sleep Habits and Emotional Symptoms: A Pilot Study Conducted in México - Paul Carrillo-Mora; Daniela M. Fonseca-Vázquez; Katia Magaña-Vázquez; Jimena Ramírez-Peris (Sleep and Vigilance, 2021)

Assessment of genetic diversity of pumpkins (Cucurbita spp.) from western Kenya using SSR molecular markers - Lameck A. Nyabera; Inosters W. Nzuki; Steven M. Runo; Peris W. Amwayi (Molecular Biology Reports, 2021)

Conservation values of understory vascular plants in even- and uneven-aged Nothofagus antarctica forests - Guillermo J. Martínez Pastur; Yamina M. Rosas; Juan M. Cellini; Marcelo D. Barrera; Mónica DR Toro Manríquez; Alejandro Huertas Herrera; Santiago Favoretti Bondar; María V. Lencinas; Pablo L. Peri (Biodiversity and Conservation, 2020)

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

Dominant native and non‐native graminoids differ in key leaf traits irrespective of nutrient availability - Arthur A. D. Broadbent; Jennifer Firn; James M. McGree; Elizabeth T. Borer; Yvonne M. Buckley; W. Stanley Harpole; Kimberly J. Komatsu; Andrew S. MacDougall; Kate H. Orwin; Nicholas J. Ostle; Eric W. Seabloom; Jonathan D. Bakker; et al. (Global Ecology and Biogeography, 2020)
Aim Nutrient enrichment is associated with plant invasions and biodiversity loss. Functional trait advantages may predict the ascendancy of invasive plants following nutrient enrichment but this is rarely tested. Here, we investigate (a) whether dominant native and non‐native plants differ in important morphological and physiological leaf traits, (b) how their traits respond to nutrient addition, and (c) whether responses are consistent across functional groups. Location Australia, Europe, North America and South Africa. Time period 2007–2014. Major taxa studied Graminoids and forbs. Methods We focused on two types of leaf traits connected to resource acquisition: morphological features relating to light‐foraging surfaces and investment in tissue (specific leaf area, SLA) and physiological features relating to internal leaf chemistry as the basis for producing and utilizing photosynthate. We measured these traits on 503 leaves from 151 dominant species across 27 grasslands on four continents. We used an identical nutrient addition treatment of nitrogen (N), phosphorus (P) and potassium (K) at all sites. Sites represented a broad range of grasslands that varied widely in climatic and edaphic conditions. Results We found evidence that non‐native graminoids invest in leaves with higher nutrient concentrations than native graminoids, particularly at sites where native and non‐native species both dominate. We found little evidence that native and non‐native forbs differed in the measured leaf traits. These results were consistent in natural soil fertility levels and nutrient‐enriched conditions, with dominant species responding similarly to nutrient addition regardless of whether they were native or non‐native. Main conclusions Our work identifies the inherent physiological trait advantages that can be used to predict non‐native graminoid establishment, potentially because of higher efficiency at taking up crucial nutrients into their leaves. Most importantly, these inherent advantages are already present at natural soil fertility levels and are maintained following nutrient enrichment.

Nutrient availability controls the impact of mammalian herbivores on soil carbon and nitrogen pools in grasslands - Judith Sitters; E. R. Jasper Wubs; Elisabeth S. Bakker; Thomas W. Crowther; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Lori Biederman; Elizabeth T. Borer; Elsa E. Cleland; Nico Eisenhauer; Jennifer Firn; et al. (Global Change Biology, 2020)
Grasslands are subject to considerable alteration due to human activities globally, including widespread changes in populations and composition of large mammalian herbivores and elevated supply of nutrients. Grassland soils remain important reservoirs of carbon (C) and nitrogen (N). Herbivores may affect both C and N pools and these changes likely interact with increases in soil nutrient availability. Given the scale of grassland soil fluxes, such changes can have striking consequences for atmospheric C concentrations and the climate. Here, we use the Nutrient Network experiment to examine the responses of soil C and N pools to mammalian herbivore exclusion across 22 grasslands, under ambient and elevated nutrient availabilities (fertilized with NPK + micronutrients). We show that the impact of herbivore exclusion on soil C and N pools depends on fertilization. Under ambient nutrient conditions, we observed no effect of herbivore exclusion, but under elevated nutrient supply, pools are smaller upon herbivore exclusion. The highest mean soil C and N pools were found in grazed and fertilized plots. The decrease in soil C and N upon herbivore exclusion in combination with fertilization correlated with a decrease in aboveground plant biomass and microbial activity, indicating a reduced storage of organic matter and microbial residues as soil C and N. The response of soil C and N pools to herbivore exclusion was contingent on temperature – herbivores likely cause losses of C and N in colder sites and increases in warmer sites. Additionally, grasslands that contain mammalian herbivores have the potential to sequester more N under increased temperature variability and nutrient enrichment than ungrazed grasslands. Our study highlights the importance of conserving mammalian herbivore populations in grasslands worldwide. We need to incorporate local‐scale herbivory, and its interaction with nutrient enrichment and climate, within global‐scale models to better predict land–atmosphere interactions under future climate change.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The complete chloroplast genomes of two species in threatened monocot genus Caldesia in China - Virginia M. Mwanzia; John M. Nzei; Dong-Ying Yan; Peris W. Kamau; Jin-Ming Chen; Zhi-Zhong Li (Genetica, 2019)

Lifestyle genomics and the metabolic syndrome: A review of genetic variants that influence response to diet and exercise interventions - Peri H. Fenwick; Khursheed Jeejeebhoy; Rupinder Dhaliwal; Dawna Royall; Paula Brauer; Angelo Tremblay; Doug Klein; David M. Mutch (Critical Reviews in Food Science and Nutrition, 2019)

Sensitivity of global soil carbon stocks to combined nutrient enrichment - T. W. Crowther; C. Riggs; E. M. Lind; E. T. Borer; E. W. Seabloom; S. E. Hobbie; J. Wubs; P. B. Adler; J. Firn; L. Gherardi; N. Hagenah; K. S. Hofmockel; et al. (Ecology Letters, 2019)
Soil stores approximately twice as much carbon as the atmosphere and fluctuations in the size of the soil carbon pool directly influence climate conditions. We used the Nutrient Network global change experiment to examine how anthropogenic nutrient enrichment might influence grassland soil carbon storage at a global scale. In isolation, enrichment of nitrogen and phosphorous had minimal impacts on soil carbon storage. However, when these nutrients were added in combination with potassium and micronutrients, soil carbon stocks changed considerably, with an average increase of 0.04 KgCm −2 year −1 (standard deviation 0.18 KgCm −2 year −1 ). These effects did not correlate with changes in primary productivity, suggesting that soil carbon decomposition may have been restricted. Although nutrient enrichment caused soil carbon gains most dry, sandy regions, considerable absolute losses of soil carbon may occur in high‐latitude regions that store the majority of the world's soil carbon. These mechanistic insights into the sensitivity of grassland carbon stocks to nutrient enrichment can facilitate biochemical modelling efforts to project carbon cycling under future climate scenarios.

Thinking in the sustainability of Nothofagus antarctica silvopastoral systems, how differ the responses of seedlings from different provenances to water shortage? - Héctor A. Bahamonde; D. Sánchez-Gómez; J. Gyenge; P. L. Peri; J. M. Cellini; I. Aranda (Agroforestry Systems, 2019)

Spatial heterogeneity in species composition constrains plant community responses to herbivory and fertilisation - Dorothee Hodapp; Elizabeth T. Borer; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Juan Alberti; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Marc Cadotte; Elsa E. Cleland; et al. (Ecology Letters, 2018)
Environmental change can result in substantial shifts in community composition. The associated immigration and extinction events are likely constrained by the spatial distribution of species. Still, studies on environmental change typically quantify biotic responses at single spatial (time series within a single plot) or temporal (spatial beta diversity at single time points) scales, ignoring their potential interdependence. Here, we use data from a global network of grassland experiments to determine how turnover responses to two major forms of environmental change – fertilisation and herbivore loss – are affected by species pool size and spatial compositional heterogeneity. Fertilisation led to higher rates of local extinction, whereas turnover in herbivore exclusion plots was driven by species replacement. Overall, sites with more spatially heterogeneous composition showed significantly higher rates of annual turnover, independent of species pool size and treatment. Taking into account spatial biodiversity aspects will therefore improve our understanding of consequences of global and anthropogenic change on community dynamics.

Ten years of seed production and establishment of regeneration measurements in Nothofagus antarctica forests under different crown cover and quality sites, in Southern Patagonia - Héctor A. Bahamonde; M. V. Lencinas; G. Martínez Pastur; L. Monelos; R. Soler; P. L. Peri (Agroforestry Systems, 2018)

Localization of Defensive Chemicals in Two Congeneric Butterflies (Euphydryas, Nymphalidae) - Peri A. Mason; M. Deane Bowers (Journal of Chemical Ecology, 2017)

Above-ground arthropod community structure and influence of structural-retention management in southern Patagonian scrublands, Argentina - F. J. Sola; P. L. Peri; L. Huertas; G. J. Martínez Pastur; M. V. Lencinas (Journal of Insect Conservation, 2016)

Biodiversity potential of Nothofagus forests in Tierra del Fuego (Argentina): tool proposal for regional conservation planning - Guillermo Martínez Pastur; Pablo L. Peri; Rosina M. Soler; Stefan Schindler; María Vanessa Lencinas (Biodiversity and Conservation, 2016)

New ambrosia beetles (Coleoptera: Curculionidae: Platypodinae) from Miocene Mexican and Dominican ambers and their paleobiogeographical implications - David Peris; Mónica M. Solórzano Kraemer; Enrique Peñalver; Xavier Delclòs (Organisms Diversity & Evolution, 2015)

Morphological and Genetic Variations of the Freshwater Leech, Hirudinaria spp., in Peninsular Malaysia - L. K. Chong; Alan H. K. Ong; S. G. Tan; K. A. S. Taranjeet; M. M. Peris; A. M. M. A. Sana; H. R. Hassan (Biochemical Genetics, 2014)

Loss of Intrinsic Organization of Cerebellar Networks in Spinocerebellar Ataxia Type 1: Correlates with Disease Severity and Duration - Ana Solodkin; Eitan Peri; E. Elinor Chen; Eshel Ben-Jacob; Christopher M. Gomez (The Cerebellum, 2011)

Complex effects of parasitoids on pharmacophagy and diet choice of a polyphagous caterpillar - Angela M. Smilanich; Peri A. Mason; Lucy Sprung; Thomas R. Chase; Michael S. Singer (Oecologia, 2011)

Do light and alfalfa responses to cloth and slatted shade represent those measured under an agroforestry system? - A. C. Varella; D. J. Moot; K. M. Pollock; P. L. Peri; R. J. Lucas (Agroforestry Systems, 2011)

Family cancer history and risk of brain tumors in children: results of the SEARCH international brain tumor study - Susan Searles Nielsen; Beth A. Mueller; Susan Preston-Martin; Elizabeth A. Holly; Julian Little; Paige M. Bracci; Margaret McCredie; Rafael Peris-Bonet; Sylvaine Cordier; Graziella Filippini; Flora Lubin (Cancer Causes & Control, 2008)

Increasing the Knowledge of Heavy Metal Contents and Sources in Agricultural Soils of the European Mediterranean Region - M. Peris; L. Recatalá; C. Micó; R. Sánchez; J. Sánchez (Water, Air, & Soil Pollution, 2008)

Changing Epidemiology of Dengue Fever in Travelers to Thailand - E. Schwartz; A. Moskovitz; I. Potasman; G. Peri; Z. Grossman; M. L. Alkan (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Helminth parasite communities of the conger eel in the estuaries of Arousa and Muros (Galicia, north‐west Spain) - M. L. Sanmartín; M. F. Alvarez; D. Peris; R. Iglesias; J. Leiro (Journal of Fish Biology, 2000)
The nematodes Cucullanus hians, Cucullanus longispiculum , Cucullanus minutus , Contracaecum sp., Anisakis simplex , and Cristitectus congeri , the cestodes Grillotia , sp. and Scolex pleuronectis , and the acanthocephalan Acanthocephaloides propinquus , were recorded from 251 conger eels from the Muros and Arousa estuaries, north‐west Spain. Several species were useful as tags and showed that conger eels in both estuaries and also on the continental shelf belong to separate populations. The nematode C. congeri , shows a distribution pattern indicating that the trophic chains involving the conger eel in each estuary are probably different. The species composition and abundance of the nematode, cestode and acanthocephalan fauna of Conger conger , on the north‐west Spanish coast may depend more on population isolation and variations in trophic chains between the sites studied than on the particular environmental conditions of the sites.

Parental occupation, occupational exposure to solvents and polycyclic aromatic hydrocarbons and risk of childhood brain tumors (Italy, France, Spain) - S. Cordier; B. Lefeuvre; G. Filippini; R. Peris-Bonet; M. Farinotti; G. Lovicu; L. Mandereau (Cancer Causes & Control, 1997)